A Critical Analysis of Cyber Security Threats posed by Covid- 19: Designing a Roadmap for Future - Niteesh Kumar Upadhyay; Mahak Rathee (Medicine, Law & Society, 2022)
The entire world has been impacted by Covid-19, which has forced the nations to undergo lockdowns, which have opened the new horizons of virtual learning and work from home culture. Though virtual learning and online meetings were available prior to the lockdowns, use of these platforms have intensified. There is a lack of awareness among many in the public concerning the perils of using these platforms which makes them susceptible to cyber-crime attacks phishing, sexual or verbal abuse, eve teasing etc. Lockdowns have provided cyber criminals with new criminal opportunities and evidence shows that there has been a rampant increase in the number of cyber-crimes during this period. Public lack of awareness has led to innocent people falling prey in the hands of attackers. Since the pandemic and ensuing lockdowns came as a surprise, public and private authorities lacked the opportunity to make appropriate arrangements for training people and making these platforms secure. There is no question that if these platforms are made secure, then they will prove to be as an asset to the society but much work must be done to achieve the goal of complete cyber security.